KAJIAN MANAJEMEN KUNJUNGAN DI KAWASAN WISATA: STUDI KASUS DESTINASI WISATA KALIURANG - Susetyarini, Oktari (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2017)
Tourism has become an industry that can enhance the economic growth in Indonesia. The develop of tourism sector as superior sector in Sleman District has supported by many tourism products. As one of the main tourist destinations in Yogyakarta, Kaliurang has many attractions that can be offered to satisfy the traveller’s need. Recognizing the potential of Kaliurang, it is necessary followed by optimizing condition of Kaliurang. Development of good visit management concept would optimize the traveller deployment in visiting all the attractions. Visit management is an opportunity to influence the movement of visitors, meet the needs of visitors, encouraging the spread of visits evenly and provide the best travel experience. Keywords: tourism, visit management, tourism product